Flexible coaxial fiber-shaped asymmetric supercapacitors based on manganese, nickel co-substituted cobalt carbonate hydroxides. Issue 4 (3rd January 2020) - Cao, Xueying; Liu, Ying; Zhong, Yuxue; Cui, Liang; Zhang, Aitang; Razal, Joselito M.; Yang, Wenrong; Liu, Jingquan
Abstract : A wearable coaxial fiber-shaped asymmetric supercapacitor based on well-aligned Mn, Ni co-substituted Co carbonate hydroxide nanoneedle arrays on carbon fibers is successfully fabricated, and it exhibits excellent electrochemical performances. Abstract : Flexible electronic devices constitute a rapidly rising industry since they can potentially renovate the way humans communicate and interact with external environments. Recently, flexible fiber-shaped supercapacitors have shown great potential in wearable and portable electronics. Herein, a new type of flexible coaxial fiber-shaped asymmetric supercapacitor (FASC) is successfully constructed utilizing a well-aligned Mn, Ni co-substituted Co carbonate hydroxide nanoneedle array on a carbon fiber (MnNiCo-CH/CF) as the positive electrode and an activated carbon (AC) as the negative electrode. Impressively, the MnNiCo-CH/CF electrode with a hierarchical nanostructure exhibits a high specific capacitance of 1440.52 F g −1 at 1 A g −1 and superb cycling stability (90.78%), while the as-fabricated coaxial FASC exhibits a large specific capacitance of 96.13 F g −1 (1 A g −1 ) and a high energy density of 30.04 W h kg −1 at a power density of 749.97 W kg −1 . Moreover, the integration of a few FASCs in series or in parallel is demonstrated to meet the energy and power needs in various practical applications, such as powering shunt-wound LEDs or stitching into cotton fabrics to charge LED electronic displays. Therefore, the successful fabrication of practicable and ultra-flexible FASCs may realize broad applications in future flexible energy storage devices.